Analysis of MCL-1 Copy Number Variation in Non-Small Cell Lung Cancer - Almahdi Alzaroukh Jaber; Howard Pringle; David Guttery; Aesa Alzaroug Jaber (Indian Journal of Forensic Medicine & Toxicology, 2021)
Amplification of the MCL-1 gene induces MCL-1 overexpression, which is an important marker for drug resistance in several malignancies through evasion of apoptosis. We analysed 39 lung adenocarcinomas (ADCs), 38 lung squamous cell carcinomas (SCCs), two large cell lung carcinomas (LCCs) and cell lines. A duplex ratio test TaqMan qPCR approach was performed for MCL-1 copy number change analysis and we demonstrated amplification of MCL-1 in H1395 cell line and copy number gain (isochromosome) in H2342 cell line. Immunohistochemistry (IHC) and in situ hybridization (ISH) were performed for protein and mRNA analysis respectively. MCL-1 amplification was detected in 13% and 2.5% of SCCs and ADCs respectively. MCL-1-amplified tumours demonstrated high expression of MCL-1 mRNA. Copy number gain was detected in 2.5 % of ADC but not SCC.